Effect of hydrocarbons on hydrogen chloride removal from refinery off-gas using zeolite NaY - Tolentino, Christina May C. (College of Engineering, University of the Philippines Diliman, 2013)
The effect of light alkanes, alkenes, and liquid aromatic hydrocarbons on the removal of HCI contaminating refinery off-gas was evaluated in this study. Zeolite NaY with molar ratio of Na2O : AbO3 : 3.19 SiO2 was synthesized using rice husk silica, pelletized to a surface area of 590 m2/g, and used as HCI adsorbent. HCI adsorption experiments were performed in a fixed-bed column operated under feed conditions of 600 ppm HCI concentration and 6401hr gas hourly space velocity. The HCI adsorption potentials on adsorbent weight basis (Wb) of pelletized zeolite NaY were calculated via the breakthrough curves. Light alkanes mixed with hydrogen decreased the adsorption potential by 3.5% (Wb = 0.1379 g HCl/g), alkenes increased the adsorption potential by I %, while soaking the zeolite NaY in aromatic liquid lowered the performance by up to 13% (Wb = 0.1247 g HCl/g). Zeolite NaY showed consistently higher performance for HCI removal compared with a commercial adsorbent (Wb = 0.0893 g HCl/g) for hydrogen feed mixed with light hydrocarbons and/or aromatics. X-ray diffraction analysis of spent adsorbent revealed the formation of sodium chloride confirming that chemisorption in addition to physisorption were the mechanisms of HCI removal.